Synthesis and Molecular Docking Studies of Pyrazolylpyrazoline-Clubbed Triazole and Tetrazoles. (International Journal of Latest Technology in Engineering Management & Applied Science, 2025)
To increase the antitubercular potency, we synthesized a series of novel pyrazolylpyrazoline derivatives (9a−n) using the one-pot multi component reaction of the substituted hetero aryl aldehyde (3a,b), 2-acetyl pyrrole/thiazole (4a,b),and substituted hydrazine hydrates(5−8) in the presence of base KOH as a catalyst in ethanol as the solvent at room temperature. Substituted hetero aryl aldehyde (3a,b) was synthesized from 5-chloro-3-methyl-1-phenyl-1H-pyrazole-4 methyl-carbaldehyde by treatment with 4-amino triazole/5-amino tetrazole. 5-Chloro-4-(1,3-dioxolan-2-yl)-3-methyl-1-phenyl-1H-pyrazole (1) was reacted with 4H-1,2,4-triazol-4-amine (a) and 1H-tetrazol-5-amine (b) in the presence of K2CO3 in 1,4-dioxane at 80 °C for 13 h. Similarly, 5-((4H-1,2,4-triazol-4-yl)amino)-3-methyl-1-phenyl-1H-pyrazole-4-carbaldehyde (3a) and 5-((1H-tetrazol-5-yl)amino)-3-methyl-1-phenyl-1H-pyrazole-4-carbaldehyde (3b) were achieved further reacted with 2-acetyle thiophene (4a) and 2-acetyle furan (4b) and substituted hydrazide derivatives (5–8) in the presence of 50% ethanolic KOH solution at room temperature All of the compounds were tested against Mycobacteriumtuberculosis H37Rv, Theoretical results were in good accord with the observed experimental values. The docking score of the most active compound 9n was found good Glide energy .